2021
DOI: 10.1016/j.heliyon.2021.e07159
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Saccharomyces Cervisciae Cell Wall Extract against thioacetamide-induced liver fibrosis in rats

Abstract: Fibrosis represents a common outcome of almost all chronic liver diseases and leads to an impairment of liver function that requires medical intervention. The current study aimed to evaluate the potential anti-fibrotic effect of Saccharomyces cervisciae cell wall extract (SCCWE) against thioacetamide (TAA)-induced liver fibrosis in rats (200mg/kg b.w. i.p. twice weekly for 6 weeks) using Ursodeoxycholic acid (UDCA) as a reference anti-fibrotic product. SCCWE at two doses (50 and 100 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 81 publications
0
1
0
1
Order By: Relevance
“…As well, Zhao et al [ 51 ] reported that AFB1 decreases Nrf2 protein levels in broiler livers. El-Gendy et al [ 84 ] reported that Nrf2 protein levels significantly increased in aflatoxicated-birds supplemented with Saccharomyces cell wall. In addition, Zaki et al [ 85 ] concluded that there was a decrease in Nrf2 protein levels with the use of curcumin and nanocurcumin compared to that of deltamethrin-treated rats, and this is what our study proves.…”
Section: Discussionmentioning
confidence: 99%
“…As well, Zhao et al [ 51 ] reported that AFB1 decreases Nrf2 protein levels in broiler livers. El-Gendy et al [ 84 ] reported that Nrf2 protein levels significantly increased in aflatoxicated-birds supplemented with Saccharomyces cell wall. In addition, Zaki et al [ 85 ] concluded that there was a decrease in Nrf2 protein levels with the use of curcumin and nanocurcumin compared to that of deltamethrin-treated rats, and this is what our study proves.…”
Section: Discussionmentioning
confidence: 99%
“…The activation and proliferation of HSCs and fibrotic tissues are regulated by reactive oxygen species (ROS) and inflammatory cytokines [7]. The activation of HSCs leads to increased expression of fibrotic biomarkers, such as alpha-smooth muscle actin (α-SMA) and autotaxin (ATX) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thioacetamide(TAA)는 동물모델에서 간섬유화를 유도하는 데 일반적으로 사용되고 있는 간독소 물질 이다 5 . TAA 자체로는 간에 독성이 없으나 활성산소종 (Reactive oxygen species, ROS)인 thioacetamide-S-oxide 를 매개로 하여 공유결합에 의해 간 세포의 손상 과 괴사가 유발된다 6 .…”
unclassified